Effect of hybrid blood purification treatment for patients with maintenance haemodialysis - Zhang, Ting; Zhang, Cuiping (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the effect of hybrid blood purification treatment on levels of serum molecular toxins, micro-inflammatory mediators and quality of life in maintenance haemodialysis patients. Method: The analytical study was conducted at the Fifth Affiliated Hospital of Xinjiang Medical University, China, from January 2019 to January 2021, and adult maintenance haemodialysis patients of either gender who were having dialysis at least 3 times per week for at least 4 h each time. The patients were randomised into two equal groups. Group A received pure haemodialysis, while Group B was given hybrid blood purification treatment. Serum parathyroid hormone, Beta 2 microglobulin, high-sensitivity C-reactive protein and interleukin-6 were determined. Kidney disease target areas and short-form 36 scores were compared between the groups. All parameters were assessed at baseline and after 3 months of intervention. Data was analysed using SPSS 25. Results: Of the 216 patients, 108(50%) were in each of the two groups. Overall, there were 120(55.6%) male and 96(44.4%) female subjects; mean age was 58.50±6.73 years; and mean dialysis duration was 31.92±5.05 months. At baseline, none of the study parameters were significantly different between the groups (p>0.05). Post-intervention, all parameters were lower in Group B compared to Group A (p<0.05). Conclusion: Compared to haemodialysis alone, hybrid blood purification treatment. I was found to be more effective in removing molecular toxins from haemodialysis patients’ blood, reducing serum micro-inflammatory status, and improving their quality of life. Key Words: Maintenance haemodialysis, Hybrid blood purification treatment, HBPT, Micro-inflammatory, Quality of life.